CEOs' talk of sustainability: Towards an inclusion of an embeddedness and value-creation perspective - Susanne Arvidsson (Lund University, School of Economics and Management, LUSEM Sustainability Research Network, 2019)
Purpose: This paper sets out to examine how CEOs' talk of sustainability has developed in a period of increased expectations from society for companies to step up their transformation towards more sustainable businesses and better account for their progress and performance within the sustainability area. Design/methodology/approach: By adopting an interpretive textual approach, this paper provides a careful analysis of how CEO talk of sustainability has developed in the largest listed Swedish companies during the period 2008-2017. The analysis focuses on the CEO letter. Findings: The CEOs' talk of sustainability is becoming much more elaborated, proactive and also adopts a multidimensional approach towards sustainability. The CEOs frame their talk by adopting different perspectives over the period; the sticky environmental-, the performance and meso-, the product-market oriented- and the embeddedness and value-creation perspective. The most intriguing finding is that of a radical change in the CEOs' talk of sustainability in the latest letters indicating that the alleged capitalistic and short-sighted focus on value maximization and profitability might be changing for embedding more of sustainability dimensions. Practical implications: The findings provide relevant inputs to the debate on how CEOs provide accountability to their stakeholders by framing their talk of sustainability from different perspectives. Originality/value: This comprehensive analysis of how CEOs in the largest listed companies through their talk of sustainability provide accountability to their stakeholders, offers a unique frame of reference for further interpretational work on how CEOs frame, engage in and shape the sustainability discourse.
Keywords: Q01; M14; M41; 330; CEO talk; sustainability; CEO letters; accountability; organisational (managerial) attention; corporate response